2012
DOI: 10.1063/1.4764880
|View full text |Cite
|
Sign up to set email alerts
|

Defect assistant band alignment transition from staggered to broken gap in mixed As/Sb tunnel field effect transistor heterostructure

Abstract: Articles you may be interested inTunneling field-effect transistor with Ge/In0.53Ga0.47As heterostructure as tunneling junction J. Appl. Phys. 113, 094502 (2013) The compositional dependence of effective tunneling barrier height (E beff ) and defect assisted band alignment transition from staggered gap to broken gap in GaAsSb/InGaAs n-channel tunnel field effect transistor (TFET) structures were demonstrated by x-ray photoelectron spectroscopy (XPS). High-resolution x-ray diffraction measurements revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The theoretical insights of staggered heterojunction (HETJ) based TFETs to achieve S < 60mv/dec at room temperature with an improved I ON has been already reported [26][27][28]. Among various III-V based staggered heterostructures, the bandgap and band alignment of the mixed As/Sb based heterostructures can be tailored-made over a wide range by carefully controlling the alloy compositions in the mixed As/Sb material system [29]. Thus, mixed As/Sb Inx Ga1-x As/GaAsySb1-y staggered gap heterostructure appears to be one of the most promising material system to boost the TFET performance due to its superior device performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical insights of staggered heterojunction (HETJ) based TFETs to achieve S < 60mv/dec at room temperature with an improved I ON has been already reported [26][27][28]. Among various III-V based staggered heterostructures, the bandgap and band alignment of the mixed As/Sb based heterostructures can be tailored-made over a wide range by carefully controlling the alloy compositions in the mixed As/Sb material system [29]. Thus, mixed As/Sb Inx Ga1-x As/GaAsySb1-y staggered gap heterostructure appears to be one of the most promising material system to boost the TFET performance due to its superior device performance.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, OFF-state current I OFF will increase and I ON /I OFF will decrease. Moreover, due to increased interface trap densities, trap assisted tunneling (TAT) current will increase, causing an enhancement in the OFF-state leakage current [29], thus causing a reduction in the I ON /I OFF ratio and subthreshold swing degradation.…”
Section: Introductionmentioning
confidence: 99%
“…A proper switching sequence of III/V elements is critical for engineering an abrupt hetero-interface during the growth of mixed As/Sb materials, [25][26][27] otherwise the intermixing between As and Sb atoms will result in uncontrolled layer composition at the hetero-interface, which will cause the change of strain relaxation properties of the epilayer grown on this interface. 28 The change of strain relaxation properties may introduce high density dislocations at the hetero-interface and within the InAs source layer, which explains the high I OFF in the fabricated hetJ pTFET. Besides, the formation of GaAs 0.022 Sb 0.978 layer at the hetero-interface will change the band alignment of source/channel, which leads to the increase of tunneling distance and degrade the device performance.…”
Section: Optimisation and Characterisation Of High-j/gasb Interfacementioning
confidence: 99%
“…2 E g,eff is usually determined from the electron affinities and bandgaps of the bulk materials, 3 or using optical measurements. 4,5 However, there is significant uncertainty on E g,eff , especially for the heterostructure In 0.53 Ga 0.47 As/ GaAs 0.5 Sb 0.5 (InGaAs/GaAsSb, Fig. 1), which makes the prediction of TFET performance difficult.…”
mentioning
confidence: 99%
“…5 for a In 0.7 Ga 0.3 As/ GaAs 0.35 Sb 0.65 heterojunction. It was reported that a fixed positive charge of 6 Â 10 12 cm À2 changed the band alignment from staggered to broken.…”
mentioning
confidence: 99%